The Association Between Money and Opinion in Academic Emergency Medicine - Birkhahn, Robert H. (Department of Emergency Medicine, University of California, Irvine School of Medicine, 2010)
OBJECTIVES: Financial conflicts of interest have come under increasing scrutiny in medicine, but their impact has not been quantified. Our objective was to use the results of a national survey of academic emergency medicine (EM) faculty to determine if an association between money and personal opinion exists. METHODS: We conducted a web-based survey of EM faculty. Opinion questions were analyzed with regard to whether the respondent had either 1) received research grant money or 2) received money from industry as a speaker, consultant, or advisor. Responses were unweighted, and tests of differences in proportions were made using Chi-squared tests, with p<0.05 set for significance. RESULTS: We received responses from 430 members; 98 (23%) received research grants from industry, while 145 (34%) reported fee-for-service money. Respondents with research money were more likely to be comfortable accepting gifts (40% vs. 29%) and acting as paid consultants (50% vs. 37%). They had a more favorable attitude with regard to societal interactions with industry and felt that industry-sponsored lectures could be fair and unbiased (52% vs. 29%). Faculty with fee-for-service money mirrored those with research money. They were also more likely to believe that industry-sponsored research produces fair and unbiased results (61% vs. 45%) and less likely to believe that honoraria biased speakers (49% vs. 69%). CONCLUSION: Accepting money for either service or research identified a distinct population defined by their opinions. Faculty engaged in industry-sponsored research benefitted socially (collaborations), academically (publications), and financially from the relationship.